Effects of solid backfilling on overburden strata movement in shallow depth longwall coal mines in West China - Spearing, A.; Huang, P.; Spearing, Sam; Feng, J.; Jessu, Kashi; Guo, S. (Institute of Physics Publishing Ltd., 2018)
© 2018 Sinopec Geophysical Research Institute. Overburden strata movement can create problems in longwall coal mines at shallow depths located in the West of China, due to surface subsidence affecting the surface structures and sensitive land features. Solid backfill mining (SBM) has been successfully used in several mines to solve many subsidence related problems, including coal extraction under buildings, water bodies and railways, and protecting the sensitive landscape. Due to the relatively shallow depth of coal seam, however, the solid backfilling materials must have high compactibility (i.e. be stiff). Based on the longwall working face 15 061 in the Dong Ping coal mine, the different size of the backfill gangue and the affects of porosity, stress and strain, strain energy density and strain were obtained in the laboratory. The deformation and energy absorb of the gangue with different particle size during compaction were analyzed. A multi-layer, composite and elastic foundation mechanical model of the key layers in the shallow coal seam was built. The compression modulus of the backfilling samples with different particle size was obtained with which the bending deflection, stress and strain energy density expression of the critical layer under different particle size range were derived. The result shows that when adopting SBM with longwall in the mine coal seam, the gangue backfilling body can effectively reduce the deformation of the key layer and absorb the energy accumulated in the key layer during the bending process. It was determined that when the gangue particle size is less than 31.5 mm (the porosity is less than 32.9%), the key layer will not break and the gangue filling body can effectively absorb 99% of the energy during the key layer bending. Whilst a smaller backfill (gangue) particle size reduces the porosity thus improving the strength, the cost of the backfill increases and this must too be considered when deciding on the material specifications. The roof deformation and fracturing in the key strata were monitored during mining in the Dong Ping coal mine site. The roof was found to be deflected but with no tensile cracking of the key immediate roof strata, showing the successful implementation of SBM.